Strategi Pengembangan Perpustakaan Nagari di Perpustakaan Nagari Kelurahan Kampung Jawa Kota Solok - Putra, Eko Tri; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
Writing this article aims to describe: (1) development strategy village library to increase public interest in the Library Nagari Solok Kampung Jawa; (2) constraints and efforts are found in increasing public interest in the village of Kampung Jawa Solok; Data were collected through direct observation and interviews with librarians Library Nagari Kampung Solok City Java. Analyzing data descriptively. Based on analyzing the data, we can conclude it - as follows. First, the library development strategy to increase public interest in reading has been done, it can be seen from the activities carried out by the library as read poetry competition elementary level, bookmobile, creating an atmosphere of reading, and library exhibitions. Second, problems were found in increasing public interest in the Library Nagari Kampung Solok City Java are: (1) the lack of library collections; (2) a library room that has not been ideal; (3) lack of human resources. Third, efforts are being made to increase public interest are: (1) increase the collection of library materials; (2) creating an ideal library room, because there is no barrier between the reading rooms, shelves and space collection librarian; (3) adding human resources.Â Keywords : development strategy, village library, public interest